Sella turcica variations in patients with transverse skeletal discrepancies versus patients with normal transverse relationships. a cross- sectional study - Nouran Seifeldin; Ahmed Eltimamy; Nora Al Abbady (BMC, 2023)
Abstract Background The sella turcica (ST) is a crucial landmark in orthodontics. It is utilized as a reliable predictor of future growth of the skeletal pattern, assisting in early diagnosis and promoting better treatment planning options. The goal of this research was to compare the morphology and bridging of the sella turcica in transverse maxillary deficient malocclusions and malocclusions with normal transverse relationships. Methods A total of 52 cone beam computed tomographic (CBCT) images were selected with an age range of 18-30 years. Group I comprised 26 patients previously diagnosed with transverse maxillary deficiency, while group II comprised 26 patients with normal transverse skeletal relationships. The length, depth and diameter of the ST were measured by two observers, the shape was evaluated as round, oval or flat and sellar bridging was calculated in each case. An Independent t-test was used to compare between the sellar dimensions in both groups. For assessment of bridging percentage Chi square test was used. Results The mean values of the length, depth and diameter of the sella in group I was 11.09 mm, 8.56 and 12.81 mm respectively and 10.34 mm, 8.24 and 12.38 mm in group II respectively (P ≤ 0.05). No significant differences were found between both groups in any of the sellar dimensions. The rounded ST shape was the most prevalent among both groups (59.6%). Partial ST bridging was found in only 7.7% of group I (p < 0.0001*). Complete ST bridging wasn't detected in either of the groups. Conclusions There was no correlation found between transverse maxillary deficiency and the morphology and bridging of the sella turcica.